Urochloa in Tropical Agroecosystems - Baptistella, João Leonardo Corte; de Andrade, Sara Adrián López; Favarin, José Laércio; Mazzafera, Paulo (Frontiers in Sustainable Food Systems, 2020)
Increasing biodiversity is an important issue in more secure and sustainable agriculture. Diversified systems are more resilient to climate change, environmental stresses and enhance soil health, nutrient cycling and nutrient use efficiency. In tropical agroecosystems, cover crops and intercrops are an alternative toward a more diverse and sustainable production. Urochloa spp. (syn. Brachiaria spp.) are perennial grasses, known for their high biomass production. They are commonly used as cover and companion crops in conservation agriculture in the tropics and the residues left in the field after cutting protect the soil and provide nutrient to the next crop cycle or intercropped culture. Urochloa species roots are vigorous, abundant and deep, as opposed to the more shallow and scarce roots of common crops. These traits contribute to carbon sequestration, soil organic matter stabilization and nutrient cycling. Urochloa roots also improve soil physical characteristics and influence soil nutrient dynamics, reducing nutrient losses and enhancing cycling, what is key to achieve greater nutrient use efficiency in agriculture. For instance, Urochloa root exudates can reduce nitrogen losses by denitrification and leaching through a process called biological nitrification inhibition; root exudates can mobilize recalcitrant phosphorus from soils and make it available for plant uptake; the deep roots of these grasses have the potential to recover nutrients that are virtually lost away from the root zone of other crops. This review compiles scientific progress regarding the introduction of Urochloa in agroecosystems, mainly on the aspects related to the contribution to more secure and sustainable agriculture.